Important features of expanding/contracting cylinder for Cross magneto-nanofluid flow. (April 2020) - Ali, Mehboob; Sultan, Faisal; Khan, Waqar Azeem; Shahzad, Muhammad; Arif, Hina
Highlights: Features of expanding/contracting cylinder for stagnation point flow of Cross magneto-nanofluid are considered here. Brownian motion and thermophoresis effects are addressed. Numerical solutions are obtained by considering convective heat-mass transport mechanism. Abstract: Here the mathematical model is developed to examine the behavior of expanding-contracting cylinder for Cross fluid flow with nanoparticles under a magnetic environment. More specifically, Cross nanofluid is electrically conducted through the magnetic field. Thermal radiation aspects are retained in the present analysis. Furthermore, the phenomenal aspect of the current review is to incorporate the features of Buongiorno revised relation for the stagnation point flow of Cross fluid. Mathematical modeling of the presented physical model is carried out in a cylindrical coordinate system and the formulated a system of PDEs (partial differential equations) is simplified in ODEs (ordinary differential equations). Then they are solved numerically by utilizing MATLAB tool bvp4c. Velocity, temperature, and concentration are conducted for Cross magneto-nanofluid. Outcomes of the current physical model are presented through graphical data and in tabular form. It is noted that the radius of curvature and temperature-dependent heat sink-source significantly affect heat-mass transport mechanisms for cylindrical surfaces. Furthermore, graphical analysis reveals that the velocity profile of Cross magneto-nanofluid enhances for augmented values of curvature parameter. Furthermore, this research work reveals that concentration distribution is a reducing function of Brownian moment parameters.